1988
DOI: 10.1523/jneurosci.08-11-04262.1988
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic localization of type I protein kinase C in rat Purkinje cells

Abstract: A monoclonal antibody against protein kinase C (PKC) was used for immunocytochemical studies of the type I PKC encoded by gamma-cDNA sequence (gamma-subspecies) in rat Purkinje cells. Dense gamma-subspecies-like immunoreactivity was found on the cell membrane and in the cytoplasm except within cell organelles of the perikaryon, dendrites, axon, and axon terminals. The nucleus was also stained but less heavily, and the nucleoli remained unstained. Synaptic vesicles in the axon terminals were densely stained. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(50 citation statements)
references
References 16 publications
6
43
1
Order By: Relevance
“…Among various tissues, the enzyme is most concentrated in the CNS (Minakuchi et al,198 1). Immunocytochemical and biochemical studies in this and other laboratories have revealed a differential regional and cellular localization of each PKC subspecies in the brain (Kitano et al, 1987;Hidaka et al, 1988;Huang et al, 1988;Kose et al, 1988;Saito et al, 1988Saito et al, , 1989Hosoda et al, 1989;Ito et al, 1990). Particularly, the r-PKC subspecies is found only in the CNS (Ohno et al, 1987).…”
mentioning
confidence: 68%
“…Among various tissues, the enzyme is most concentrated in the CNS (Minakuchi et al,198 1). Immunocytochemical and biochemical studies in this and other laboratories have revealed a differential regional and cellular localization of each PKC subspecies in the brain (Kitano et al, 1987;Hidaka et al, 1988;Huang et al, 1988;Kose et al, 1988;Saito et al, 1988Saito et al, , 1989Hosoda et al, 1989;Ito et al, 1990). Particularly, the r-PKC subspecies is found only in the CNS (Ohno et al, 1987).…”
mentioning
confidence: 68%
“…It has been shown that both PKC␥ and DGK␥ are abundantly expressed in Purkinje cells (12,30) and possess not only cysteine-rich regions but also calcium-sensitive domains (2). These findings suggest a functional correlation between this DG-dependent kinase and DG-catalyzing kinase.…”
Section: Discussionmentioning
confidence: 90%
“…DAG also functions as an activator for PKC. Like DAGL␣, PKC␥ is particularly abundant in Purkinje cells and activated downstream to the mGluR1 cascade (Kose et al, 1988;Nishizuka, 1992). The major mGluR1 signaling cascade in Purkinje cells, i.e., mGluR1-G␣q/11-PLC␤4 -PKC␥, is crucial for climbing fiber synapse elimination and motor coordination (Kano et al, 1995(Kano et al, , 1998Offermanns et al, 1997).…”
Section: Discussionmentioning
confidence: 99%